(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Technological advancements have a significant impact on life, especially in the business world. Businesses without technological support will lose out in the competition. One common business venture among today’s society is the home business or home industry. Home businesses run by entrepreneurs are easier to grow because they are managed personally with minimal capital and are more in touch with the surrounding community. The Chili Oil Dumpling Product is one such home business operating in the culinary or food industry. Initially, the Chili Oil Dumpling Product home business only served small-scale orders. Eventually, the Chili Oil Dumpling Product business grew and became more well-known in the surrounding community. Until now, the Chili Oil Dumpling Product home business was only known by its owner, without a brand or business name. To gain greater recognition and establish a distinctive product, the business logo was created, namely Pangsit Chili Oil. A team of DPL lecturers for community service assisted in creating the Chili Oil Dumpling Product logo using the Canva application. By creating a logo using Canva, the Chili Oil Dumpling Product home business was able to create an attractive logo easily and simply.